Synergistic coordination enhanced Janus covalent organic framework membrane as well as preparation method and application thereof

CN119638931AActive Publication Date: 2025-03-18SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411717765.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The pore sizes of existing covalent organic frame films cannot be continuously adjustable, and there are defects in crystallinity and pore structure, which makes it difficult to directly use size screening to achieve ion selective separation.

Method used

The Janus covalent organic frame film with synergistic enhanced coordination was synthesized by acetic acid buffer interlayer interface method. By adjusting the hydroxyl position, a COF film with ortho-hydroxyl configuration with synergistic coordination ability and para-hydroxyl configuration that cannot be coordinated were prepared.

Benefits of technology

In the Sr/Y separation system, the selectivity of the ortho-hydroxy COF membrane with synergistic coordination ability to Sr(II) is as high as 99.7%, and the selectivity remains above 95% after five repeated experiments, significantly improving the separation efficiency of Sr/Y.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638931A_ABST
    Figure CN119638931A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of synthesis of covalent organic framework membrane materials, and particularly relates to a synergistic coordination enhanced Janus covalent organic framework membrane as well as a preparation method and application thereof. In order to solve the problems that the pore size of the existing covalent organic framework membrane cannot be continuously adjusted, the crystallinity and the pore channel structure have defects, and ion selective separation is difficult to realize by directly adopting size screening, the invention provides a Janus covalent organic framework membrane (2D Janus COFs membrane) with enhanced coordination. The structural formula of the synergistic coordination enhanced Janus covalent organic framework film is as shown in formula I in the specification. The invention also provides an application of the synergistic coordination enhanced Janus covalent organic framework membrane in preparation of a Sr / Y separation material. The COF membrane provided by the invention has more multifunctional sites, enhances the coordination ability to Y (III), promotes the effective separation of Sr and Y, and provides a new way for the development of Sr / Y efficient separation porous materials. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of synthesis of covalent organic framework membrane materials, and in particular relates to a Janus covalent organic framework membrane with synergistic coordination enhancement, and a preparation method and application thereof. Background Art

[0002] 90 Y has a suitable half-life (T 1 / 2 = 64.1h), high energy β rays (E max = 2.28 MeV) and stable decay products, based on 90 Y radiopharmaceuticals have been widely used in the treatment of cancer with different targeted molecular radiolabeling and radiosynovectomy. 90 The main preparation method of Y is 90 Sr decays into 90 Y. However, 90 Sr is a highly toxic element with a strong bone affinity and a long half-life. According to the United States Pharmacopeia monograph, when injected 90 Y solution 90 Sr / 90 The ratio of Y should not exceed 2.0×10 -5 . Therefore, it is necessary to achieve efficient separation of Sr and Y. At present, the commonly used Sr / Y separation methods include solid phase extraction, ion exchange, solvent extraction, etc. However, based on the use of existing technologies and materials, these methods have their own defects, such as easy emulsification, easy loss of extractant, and a lot of secondary waste in liquid-liquid extraction; ion exchange has problems such as low attachment capacity, low selectivity, and high price of ion resin. Therefore, it is necessary to develop new separation materials and technologies.

[0003] Membrane separation technology combines the functions of separation, purification and concentration, and has the characteristics of simple separation process, no chemical change, no phase change, low energy consumption, strong process adaptability, and good reusability. It has good application prospects in the field of ion separation. So far, commercial membrane materials are mostly polymers, such as polytetrafluoroethylene membranes, polyvinylidene fluoride membranes, cellulose acetate membranes, polyimide membranes, etc. This type of polymer has the advantages of stability, easy processing and molding, and mature preparation technology. However, due to the limitations of the intrinsic structure of the material, there are problems such as large pore size, uneven pore distribution, difficult to control pore size, and difficulty in functionalization. It is difficult to balance permeability and selectivity, which affects the separation efficiency of the membrane. Membrane materials for ion selective separation are urgently needed to be developed.

[0004] Two-dimensional covalent organic frameworks (COFs) are a new type of organic porous crystalline material formed by small organic molecules connected by covalent bonds. Benefiting from its abundant monomers, flexible and reversible linking methods and clear reaction pathways, COFs have highly ordered periodic structures, easily adjustable pore sizes, flexibly designed active sites, and the ability to remove specific ions by modifying the internal environment of the pores. This makes COFs an effective material for manufacturing high-efficiency and selective screening membrane materials. Size screening is an important separation mechanism of current COFs membranes. For example, Banerjee et al. prepared a series of COFs membranes with pore sizes ranging from 1.4 to 2.6 nm by the water-organic solvent interface method. This series of membranes showed good solvent permeability. Dye blocking experiments showed that COFs membranes had obvious screening effects on dye molecules of different sizes. [1] However, the hydrated size of most nuclide ions is less than 1 nm, and the difference between different ion sizes is small. The pore size of most COFs membranes synthesized based on current monomer combinations and preparation methods is larger than 1 nm. Limited by the size and symmetry of the monomers, the pore size of the COF membrane cannot be continuously adjusted, making it difficult to directly use size screening to achieve ion selective separation.

[0005] In order to improve the selective separation effect of COF membranes for target ions, researchers usually use post-functionalization modification methods to graft molecules rich in active functional groups onto the surface of COF membrane materials. For example, Cao Li et al. grew ethylene-functionalized COFs membranes on commercial polyacrylonitrile membrane substrates through a three-component interfacial polymerization reaction, and modified cysteine ​​on the pores of the COFs membrane through a click reaction between ethylene and thiol to prepare amino acid-functionalized COFs membrane materials. Before the click reaction, the COFs membrane was sensitive to Na + and K + The permeation rates were 9.1 and 16.2 mmol m -2 h -1 , K + / Na + The selectivity is 1.8. After the click reaction, Na + and K + The permeation rates of COFs membranes were increased by 1.5 and 1.2 times, respectively. Since cysteine ​​contains pH-sensitive carboxyl and amino groups, and its isoelectric point is 5.02, the authors also studied the ion diffusion characteristics under two representative pH conditions, pH = 3.8 and pH = 8.9. At pH = 3.8, the COFs membrane has a strong affinity for Na + and K + The permeation rates were 12.6 and 21.4 mmol h -1 m -2 , K+ / Na + The selectivity of COFs membrane is 1.7. However, when the pH value of the solution increases to 8.9, the selectivity of COFs membrane to Na + and K + The permeation rates were 73.7 mmol h -1 m -2 and 27.3 mmol h -1 m -2 , Na + / K + The selectivity is 2.7, thus achieving Na + / K + Controllable regulation of selectivity provides a powerful platform for monovalent cation separation [2] However, the post-functionalization modification method is not only difficult to guarantee the modification rate [3-5] , and will cause the COF membrane material to lose its original good crystallinity after functionalization, resulting in an increase in amorphous state and blockage of pores, which is the main problem encountered by most post-modified COF membrane materials. Summary of the invention

[0006] In order to solve the problems that the pore size of the existing covalent organic framework membrane cannot be continuously adjusted, the crystallinity and pore structure have defects, making it difficult to directly use size screening to achieve ion selective separation, etc., the present invention provides a synergistically coordinated enhanced Janus covalent organic framework membrane (2D Janus COFs membrane). The structural formula of the above-mentioned synergistically coordinated enhanced Janus covalent organic framework membrane is shown in Formula I:

[0007]

[0008] Wherein, X is C or N, and R1 to R4 are independently -H or -OH.

[0009] Preferably, R1 to R4 are independently -H or -OH, and are not -H or -OH at the same time.

[0010] The structure of the above-mentioned synergistic coordination enhanced Janus covalent organic framework membrane is:

[0011]

[0012] The present invention also provides a method for preparing the above-mentioned synergistic coordination enhanced Janus covalent organic framework membrane (schematic diagram as shown in Figure 1 ). The preparation method of the synergistic coordination enhanced Janus covalent organic framework membrane is synthesized by an acetic acid buffer layer interface method, and the reaction formula is:

[0013]

[0014] The method for preparing the above-mentioned synergistic coordination enhanced Janus covalent organic framework membrane comprises the following specific steps:

[0015] a. Dissolve the aldehyde monomer in dichloromethane as the lower organic phase, and then slowly add acetic acid dropwise as the intermediate buffer aqueous phase;

[0016] b. Dissolve the amine monomer in DMF (N,N-dimethylformamide) solution, and then slowly drop it onto the middle buffer water phase layer as the upper organic phase layer;

[0017] c. The layered mixture is allowed to react at room temperature for 3 days, and then a solid product is obtained at the interface. The solid product is washed with water and ethanol in sequence to obtain a Janus covalent organic framework membrane with synergistic coordination enhancement.

[0018] In the preparation method of the synergistic coordination enhanced Janus covalent organic framework membrane, the mass volume ratio of the aldehyde monomer to dichloromethane in step a is 20 mg:60 mL to 60 mg:100 mL.

[0019] In the preparation method of the above-mentioned synergistic coordination enhanced Janus covalent organic framework membrane, the acetic acid in step a is 6M.

[0020] In the method for preparing the synergistically coordinated enhanced Janus covalent organic framework membrane, the mass volume ratio of the amine monomer to DMF in step b is 40 mg:30 mL to 80 mg:70 mL.

[0021] In the method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane, the molar ratio of the aldehyde monomer to the amine monomer in steps a and b is 1:1.1 to 1:1.5.

[0022] The present invention also provides the use of the synergistic coordination enhanced Janus covalent organic framework membrane in the preparation of Sr / Y separation materials.

[0023] The Janus covalent organic framework membrane with enhanced synergistic coordination provided by the present invention is synthesized by the interface method between acetic acid buffer layers. The present invention obtains two types of COF membranes by positioning hydroxyl groups at specific positions: one is an ortho-hydroxyl configuration, which can coordinate synergistically with ions; the other is a para-hydroxyl configuration, which cannot coordinate synergistically with ions. The present invention explores the influence of COF membranes with two chelating group configurations on the Sr / Y separation performance. The results show that when the number of hydroxyl groups is the same, the COF membrane with ortho-hydroxyl groups is easier to complex with Y(III) due to the additional binding sites compared with the COF membrane with para-hydroxyl groups. In the Sr / Y separation system, the COF membrane with ortho-hydroxyl groups having synergistic coordination ability has a selectivity of up to 99.7% for Sr(II). After five repeated experiments, the selectivity remains above 95%; while for the COF membrane with para-hydroxyl groups, its selectivity for Sr(II) is only 66.4%. This indicates that the COF membrane material with ortho-hydroxyl groups has more functional sites to coordinate with Y(Ⅲ), thus achieving efficient Sr / Y separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the synthesis of four 2D Janus COFs films.

[0025] Figure 2 (a) to (d) are the infrared spectra of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF films and monomers, respectively; (e) to (h) are the PXRD patterns and MS simulation patterns of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF films, respectively.

[0026] Figure 3 (a~d) Nitrogen adsorption / desorption curves, pore size distribution, MS simulated pore size, SEM images and their enlarged images of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF films, respectively.

[0027] Figure 4 (a~d) are the PXRD of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF films at different acidities, and (e~h) are the FTIR of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF films at different acidities.

[0028] Figure 5(ab) are FT-IR spectra of o-Tb COF and p-Tb COF films before and after 100-300 kGy β-ray irradiation, and (cd) are FT-IR spectra of o-Tb COF and p-Tb COF films before and after 100-300 kGy γ-ray irradiation.

[0029] Figure 6 (a~d) are the water fluxes of the COFs membrane close to the DMF solution side and the CH2Cl2 solution side, respectively. (e) is the SEM image of the o-Tb COF membrane close to the DMF solution side. (f) is the SEM image of the o-Tb COF membrane close to the CH2Cl2 solution side.

[0030] Figure 7 (a-c) are bar graphs of the separation effect of COF membrane materials at different feed concentrations (the concentration is 0.1 mmol L -1 , 0.25mmol L -1 and 0.5mmol L -1 ), (de) are the long-term concentration variation diagrams of o-Tb COF and p-Tb COF films, and (f) are the repetitive performance diagrams of o-Tb COF films.

[0031] Figure 8 SEM images of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF membranes in original state, after separation and after elution, respectively.

[0032] Fig. 9 PXRD patterns of o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF films in the original, after separation and after elution, respectively.

[0033] Fig.10 EDX images of o-Tb COF film before (a) and after (b) elution.

[0034] Fig.11 Schematic diagram of the binding functional sites of four COF membranes for Sr / Y separation.

[0035] Fig.12 (a~c) are the full XPS spectrum, O spectrum and N spectrum of o-Tb COF film material, respectively, and (d~f) are the full XPS spectrum, O spectrum and N spectrum of p-Tb COF film material, respectively (the sample after COF adsorbing Y is named COF@Y).

[0036] Fig.13 Binding energy and electrostatic potential ESP analysis of two COF configurations with yttrium nitrate (green is C; white is H; red is O; purple is N; yellow is Y). DETAILED DESCRIPTION

[0037] The preparation method of the synergistic coordination enhanced Janus covalent organic framework membrane comprises the following specific steps:

[0038] a. Dissolve the aldehyde monomer in dichloromethane as the lower organic phase, and then slowly drop 6M acetic acid as the intermediate buffer aqueous phase; the mass volume ratio of the aldehyde monomer to dichloromethane is 20mg:60mL to 60mg:100mL;

[0039] b. Dissolve the amine monomer in DMF (N,N-dimethylformamide) solution, and then slowly drop it onto the intermediate buffer aqueous phase layer as the upper organic phase layer; the mass volume ratio of the amine monomer to DMF is 40 mg:30 mL to 80 mg:70 mL;

[0040] c. The layered mixture is allowed to react at room temperature for 3 days, and then a solid product is obtained at the interface. The solid product is washed with water and ethanol in sequence to obtain a Janus covalent organic framework membrane with synergistic coordination enhancement.

[0041] In the method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane, the molar ratio of the aldehyde monomer to the amine monomer in steps a and b is 1:1.1 to 1:1.5.

[0042] Tris(4-aminophenyl)benzene (Tb), 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (Tt), 2,5-dihydroxy-terephthalaldehyde (p-CHO), and 2,3-dihydroxy-o-phthalaldehyde (o-CHO) were purchased from Shanghai Kaiyulin Pharmaceutical Technology Co., Ltd. Yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and strontium nitrate (Sr(NO3)2) were purchased from Anaiji (Shanghai) Pharmaceutical Chemistry Co., Ltd. N,N-dimethylformamide (DMF), dichloromethane, and glacial acetic acid were purchased from Chengdu Kelong Chemical Reagent Co., Ltd., China. All reagents and solvents used in this study were of the purity used without further purification.

[0043] Example 1 Synthesis of Janus covalent organic framework membranes with different synergistic coordination enhancements:

[0044]

[0045] First, o-CHO (44.08 mg, 0.26 mmol) was dissolved in 80 mL of dichloromethane as the lower organic phase, followed by slow dripping of 40 mL of 6 M acetic acid as the intermediate buffered aqueous phase, and finally Tb (61.15 mg, 0.174 mmol) was dissolved in 50 mL of DMF solution as the upper organic phase. The beaker was left to react at room temperature for 3 days. A solid product was then obtained at the interface, which was washed with water and ethanol in turn to obtain an o-Tb COF membrane.

[0046] The p-Tb COF membrane was prepared from p-CHO (44.08 mg, 0.26 mmol) and Tb (61.15 mg, 0.174 mmol) monomers using the above method.

[0047] The o-Tt COF membrane was prepared from o-CHO (44.08 mg, 0.26 mmol) and Tt (61.67 mg, 0.174 mmol) monomers using the above method.

[0048] The p-Tt COF membrane was prepared from p-CHO (44.08 mg, 0.26 mmol) and Tt (61.67 mg, 0.174 mmol) monomers using the above method.

[0049] Example 2 Characterization of Janus covalent organic framework membranes enhanced by synergistic coordination

[0050] The four COF films prepared in Example 1 of the present invention are named o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF, respectively.

[0051] 1) The formation of COF film was characterized by Fourier transform infrared (FTIR) spectroscopy. It can be seen from the FT-IR spectrum that ( Figure 2 a~d), C=O in monomer o-CHO (1653cm -1 ) characteristic absorption peak and -NH2 of monomer Tb (3210~3466cm -1 ) disappeared, 1620cm -1 New C=N stretching vibration peak signals appear around 1653 cm-1, which provide evidence for the successful condensation reaction between aldehyde and amine. Similarly, C=O (~1653 cm-1) can be observed in the infrared spectra of p-Tb COF, o-Tt COF, and p-Tt COF. -1 ) and -NH2(3200-3500cm -1 ) characteristic peak disappears and the C=N characteristic peak appears, which indicates that the three COF membranes also successfully undergo aldehyde amine condensation reaction.

[0052] Then, based on the powder x-ray diffraction (PXRD) data, the layer stacking of these COFs was simulated using Materials Studio (MS). Figure 2As shown in Figure e, the XRD diffraction peak position of o-Tb COF is consistent with the diffraction peak position of AA stacking simulated by MS. The diffraction peaks of 2.8°, 4.7°, 5.5°, 7.5° and 9.9° of o-Tb COF correspond to the (100), (110), (200), (120) and (220) crystal planes. Similarly, the XRD spectra of p-Tb COF, o-Tt COF and p-Tt COF also show that the XRD experimental diffraction peak position of COFs is consistent with the diffraction peak of AA stacking obtained by MS simulation ( Figure 2 f~h). Pawley refinement of the experimental PXRD data gave good consistency factors (Rwp=2.79%and Rp=2.08%for o-Tb COF; Rwp=3.39%and Rp=2.61%for p-Tb COF; Rwp=3.05%and Rp=5.33%for o-Tt COF; Rwp=3.13%and Rp=2.18%for p-Tt COF).

[0053] 2) Generally speaking, the pore sizes will be different depending on the stacking method of the materials. In order to further determine the stacking method of COFs materials, we performed N2 adsorption and desorption characterization on four COFs materials.

[0054] The results are as follows Figure 3 As shown, the adsorption isotherm of o-Tb COF follows the typical type IV adsorption isotherm, reflecting that the pore distribution of o-TbCOF is mesoporous. According to the non-local density functional method, it can be calculated that the average pore size of o-Tb COF is 3.0nm, which matches the pore size of AA stacking simulated by MS of 3.3nm, thus confirming that o-Tb COF adopts AA stacking. Similarly, the measured pore sizes of the other three COFs are also consistent with the simulated pore sizes. In addition, according to the N2 adsorption-desorption isotherm calculation, the specific surface areas of the four COF materials, o-Tb COF, p-Tb COF, o-Tt COF and p-Tt COF, are 184m 2 g -1 、356m 2 g -1 、878m 2 g -1 and 1253m 2 g -1 We found that the triazine-centered COF material has a significantly larger specific surface area than the benzene-centered COF material. It is speculated that this may be due to the better planarity of the amine monomer at the triazine center, which leads to a strong π-π stacking interaction between the layers of the COF material, a high crystallinity and a fixed void structure, which results in a larger specific surface area. In addition, the scanning electron microscope (SEM) image shows ( Figure 3 a and 3b), the microstructures of o-Tb COF and p-Tb COF (centered on the benzene ring) show a smooth planar structure, while o-Tt COF and p-Tt COF (centered on the triazine ring) show a ribbon morphology ( Figure 3 c and 3d). This difference originates from the effect of hydrogen bonding on the structural features: the amine monomer at the center of the triazine ring makes the benzene rings almost in the same plane, resulting in strong interlayer π-π stacking and high PXRD intensity ratio, which promotes the growth in the Z-axis direction. However, the COF film at the center of the benzene ring has weak interlayer interaction due to the layout of the benzene rings not in the same plane, which inhibits the Z-axis growth and eventually forms dense spherical crystals.

[0055] 3) Physical and chemical stability

[0056] The physical and chemical stability of the membrane is one of the important indicators to ensure the effective application of the membrane in the actual environment. The thermal stability, acid stability and radiation stability of the COF membrane were tested.

[0057] The thermal stability of COF films was determined by thermogravimetric (TGA) analysis in a N2 atmosphere. The results of thermogravimetric analysis showed that the weight loss below 100°C was caused by water evaporation, which may be related to the hydrophilicity of hydroxyl groups. The slight weight loss (about 10%) between 100 and 400°C may be caused by the decomposition of some small molecules in the material. When the temperature reached 500°C, the mass percentages of o-TbCOF film, p-Tb COF film, o-Tt COF film and p-Tt COF film remained at 66.9%, 81.5%, 76.7% and 77.6%, respectively. The results show that all four membrane materials have excellent thermal stability.

[0058] The acid stability of the COF membranes was evaluated by soaking the four membrane materials in nitric acid solutions of pH = 3, pH = 2, and pH = 1 for 72 hours. The soaked samples were filtered, washed with water, and vacuum dried before PXRD and FTIR tests.

[0059] It can be seen from the PXRD spectra that the PXRD characteristic peak positions of the four materials did not change significantly before and after immersion, and the characteristic peak positions and intensities in the FTIR spectra of the four materials did not change significantly before and after immersion, indicating that they have good acid stability ( Figure 4 ).

[0060] The present invention tests the irradiation stability of membrane materials with ortho-hydroxyl and para-hydroxyl configurations (taking o-Tb COF and p-Tb COF membranes as examples) by comparing their FT-IR spectra before and after 100-300 kGy β and γ ray irradiation ( Figure 5), and evaluated the radiation stability of these materials. The test results showed that the characteristic peak position and intensity of the FTIR spectrum of the ortho-hydroxy COF membrane material did not change significantly before and after β and γ ray irradiation, which indicates that the membrane material has good radiation stability and can withstand 300kGy of β and γ ray irradiation.

[0061] 4) Water flux

[0062] Since it was found during the experiment that the two sides of the o-Tb COF membrane have different affinities for water, the present invention studies the water flux of the o-TbCOF membrane.

[0063] The results showed that the water flux of the o-Tb COF membrane on the side close to the DMF solution was 12.45 L h -1 m -2 , the water flux on the side close to the CH2Cl2 solution is 4.16 L h -1 m -2 . This may be due to the fact that in the initial stage of the growth of the o-Tb COF film, the amine monomers in DMF react with the aldehyde monomers through the acetic acid layer, and then form a dense COF film at the acetic acid-dichloromethane interface. After the COF film is formed, the diffusion of the amine monomer into the aldehyde solution is greatly hindered because the particle size of the amine monomer is relatively larger than the pore size of COF. Not only that, the amine monomer can also react with acetic acid to form salts, which also makes it more difficult for the amine monomer to diffuse into the aldehyde solution. However, the diffusion of aldehyde monomers into the amine solution is easier because the particle size of the aldehyde is relatively small and is not affected by acetic acid. Under the catalysis of acetic acid, the amine monomers in the amine solution react with the aldehyde monomers to form COF nanoparticles. Under the action of gravity, the COF nanoparticles sink to the initially grown COF film and gradually grow into another layer of COF film. As Figure 6 As shown, the side of the COF membrane close to the DMF solution is loose, and the side close to the CH2Cl2 solution is dense.

[0064] Example 3 Separation Experiment

[0065] The abundant N and O active sites in COF membranes provide a potential environment for the separation of target ions. We propose to use the rigid skeleton of COF to precisely position functional groups at specific locations, such as the two adjacent hydroxyl groups in o-Tb COF and o-Tt COF, which can add additional binding functional sites, thereby enhancing the cooperative coordination ability of COF membranes for target ions. To verify this view, we conducted static diffusion experiments on four COF membranes with ortho-hydroxyl configurations and para-hydroxyl configurations.

[0066] 1) Liquid preparation: Weigh Y(NO3)3·6H2O (10.6 mg, 0.05 mmol) and Sr(NO3)2 (19.2 mg, 0.05 mmol) into the same beaker, then add 500 mL of deionized water with a pH of 4.5, stir and mix well to obtain an initial concentration of 0.1 mmol L -1 Similarly, a metal ion solution with a concentration of 0.25 mmol L -1 and 0.5mmol L -1 concentration of metal ion solution.

[0067] 2) Static diffusion experiment: In order to study the transport characteristics of Sr / Y in the COF membrane nanochannel, a static diffusion experiment was carried out using a U-type filter. The metal ion solution was placed on one side of the U-type filter as the feed solution, and deionized water was placed on the other side as the permeate. The metal ion concentration on the permeate side was tested to evaluate the permeation rate of the metal ions.

[0068] The present invention uses an initial concentration of 0.1 mmol L -1 A mixed ion solution of SrNO3 (strontium nitrate) and YNO3 (yttrium nitrate) was used as the feed solution. 125 mL of the above feed solution with a pH of 4.5 was added to the feed side, and deionized water of equal pH and volume was added to the permeate side. Both the feed solution and the permeate were stirred with a magnetic stirrer to avoid concentration-diffusion polarization. To monitor ion permeation, 5 mL of the permeate was taken at a fixed time and the ion concentration was determined by ICP-OES. At the same time, 5 mL of the feed solution was taken to balance the pressure. The separation effect of COF membrane material on strontium and yttrium was measured by permeation rate (mmol h -1 m -2 ) and selectivity (%) were analyzed and calculated. In order to evaluate the recycling performance of the four membrane materials, the COF membrane was eluted after the static diffusion experiment. The condition was that ethylenediaminetetraacetic acid (EDTA) disodium salt aqueous solution was added to one side of the U-shaped device and left to stand at room temperature for 24 hours. The static diffusion experiment was performed again after the residual EDTA was washed with deionized water.

[0069] The results are as follows Figure 7 As shown in a, the COF membranes with ortho-hydroxyl configuration (o-Tb COF and o-Tt COF) have excellent coordination ability for Y(Ⅲ) due to the presence of additional binding active functional sites in their structure. The selectivity for Sr(Ⅱ) in the separation process is as high as 98.4% and 94.1%, and the permeability is 0.020 and 0.080 mmol L, respectively. -1 m -2However, due to the lack of additional functional active sites, the selectivity of the COF membranes with para-hydroxyl configuration (p-Tb COF and p-Tt COF) for Sr was only 66.3% and 77.6%, and the permeabilities were 0.068 and 0.103 mmol L, respectively. -1 m -2 We also conducted static diffusion experiments by increasing the ion concentration of the feed solution. The results are as follows Figure 7 As shown in Figs. b and 7c, the permeability of Sr(Ⅱ) increases with the increase of feed solution concentration. It is worth noting that when the initial concentration of Sr / Y mixed ion solution (feed solution) increases to 0.25 and 0.5 mmol L -1 When the o-TbCOF membrane has a selectivity of 99% and 99.8% for Sr(Ⅱ), the permeability is 0.175 and 0.208 mmol L -1 m -2 The selectivity of p-Tb COF membrane for Sr(Ⅱ) was only 64.2% and 63.9%, and the permeability was 0.216 and 0.606 mmol L -1 m -2 This further verifies the view that the COF membrane with ortho-hydroxyl configuration has excellent coordination ability for Y(Ⅲ) due to its structure.

[0070] Secondly, 0.25 mmol L -1 A mixed ion solution of strontium nitrate and yttrium nitrate was used to explore the effect of time on the static diffusion experiment, and the diffusion time was extended to 144 hours. Figure 7 d. At the beginning of the diffusion experiment, the o-TbCOF membrane with ortho-hydroxyl configuration showed a strong coordination ability for Y(Ⅲ), effectively blocking most of Y(Ⅲ). This resulted in a Sr(Ⅱ) selectivity of 99% in the first 24 hours. Subsequently, when the coordination effect of the o-Tb COF membrane on Y(Ⅲ) reached saturation, Y(Ⅲ) began to gradually permeate through the COF membrane. The coordination effect of the o-Tb COF membrane on Y(Ⅲ) in the first 24 hours enhanced the Sr / Y separation effect, so that the selectivity of the o-Tb COF membrane for Sr(Ⅱ) remained above 70% even after 144 hours. However, as Figure 7 As shown in Figure e, for the p-TbCOF film with hydroxyl configuration, the selectivity for Sr is 66.8% in the first 24 hours.

[0071] Membrane reusability: Figure 7 f, in the repeated 5 static diffusion experiments, the permeability of the two COF membranes with different configurations to Sr / Y ions and the selectivity to Sr(Ⅱ) did not change much. SEM images show ( Figure 8 ), the morphology of the COF membrane did not change significantly before and after separation, and its PXRD pattern ( Fig. 9) shows that the COF film still maintains a good crystal shape, indicating that it has good mechanical stability during the experiment. And in the EDX electron image ( Fig.10 ) The disappearance of yttrium can be seen in the total number spectrum of the distribution diagram, indicating that the yttrium ions were successfully desorbed and the eluted COF membrane material can be used for the next separation experiment cycle. Finally, we conducted a static diffusion experiment with the o-Tb COF membrane after γ-ray irradiation. The selectivity of the o-Tb COF membrane for Sr(Ⅱ) remained at 91.1%. It can be seen that the selectivity of the o-Tb COF membrane for Sr ions is not greatly affected by γ-ray irradiation, which once again proves the excellent irradiation stability of the o-Tb COF membrane. Based on the above experimental results, a schematic diagram of the separation process was made ( Fig.11 ).

[0072] Example 4 Separation Mechanism

[0073] In order to reveal the interaction mechanism between Y ions and COFs, X-ray photoelectron spectroscopy (XPS) was used to study the elemental composition of the two membrane materials, ortho-hydroxyl configuration and para-hydroxyl configuration, before and after combining with Y(Ⅲ).

[0074] like Fig.12 As shown in Figures 1a and 12d, it can be observed from the high-resolution XPS spectrum of Y 3d that a new Y 3d peak appears after the static diffusion experiment, proving that Y(III) successfully coordinates with the active sites in the pores of the o-Tb COF membrane and the p-Tb COF membrane. Fig.12 c and 12f, the 1s peak of CO in the o-Tb COF film and p-Tb COF film after the separation of strontium and yttrium moves to the direction of higher binding energy, indicating that the O atoms in COFs participate in the coordination of Y(Ⅲ). The N1s spectrum of the o-Tb COF film can form two peaks at 400.3eV and 399.2eV respectively ( Fig.12 b), respectively attributed to CN and C=N. After strontium and yttrium are separated ( Fig.12 b), the peaks of CN (400.8eV) and C=N (399.5eV) shift to higher binding energies, indicating that effective coordination occurs between N atoms and Y(Ⅲ) in the o-Tb COF film. The trend of the N1s XPS spectrum change of the p-Tb COF film is consistent with that of the o-Tb COF film ( Fig.12 e).

[0075] In addition, theoretical calculations further confirm the above viewpoints, which are consistent with the experimental results. Fig.13 The binding energy of the COF film Y(Ⅲ) with ortho-phenolic hydroxyl configuration is -63.6 kcal mol -1 , while the binding energy of the COF membrane Y(Ⅲ) with para-phenolic hydroxyl configuration is -24.4 kcal mol -1, indicating that the ortho-hydroxyl configuration has stronger binding ability.

[0076] The present invention adopts the strategy of precisely adjusting the position of functional groups on the pore wall of COFs, and successfully prepares 2D Janus COF membranes with two configurations by using the acetic acid buffer layer interface method: one is an ortho-phenolic hydroxyl configuration that can coordinate with ions, and the other is a para-phenolic hydroxyl configuration that lacks such coordination ability. The effect of different coordination structures on the Sr / Y separation performance was studied. The results show that when the number of hydroxyl groups is the same, the affinity of the ortho-phenolic hydroxyl COF membrane for Y(Ⅲ) is significantly higher than that of the para-phenolic hydroxyl COF membrane, which is mainly due to the additional binding sites provided by the ortho-phenolic hydroxyl configuration. In the Sr / Y separation system, the selectivity of the ortho-phenolic hydroxyl COF membrane for Sr(Ⅱ) reached 99.7%, and the selectivity remained above 95% even after 5 cycle tests. In contrast, the selectivity of the para-phenolic hydroxyl COF membrane for Sr(Ⅱ) was only 66.4%. It shows that the COF membrane with ortho-phenolic hydroxyl has more multifunctional sites, enhances the coordination ability for Y(Ⅲ), and promotes the effective separation of Sr and Y. The present invention provides a new approach for the development of porous materials for efficient Sr / Y separation.

[0077] References:

[0078] [1] K. Dey, M. Pal, KCRout, S. Kunjattu H, A. Das, R. Mukherjee, UK Kharul, R. Banerjee, Selective Molecular Separation by Interfacially CrystallizedCovalent Organic Framework Thin Films, J. Am. Chem. Soc. 139 (2017) 13083–13091.

[0079] [2] L.Cao, I.-C.Chen, Z.Li,

[0080] [3]H.L.Nguyen,C.Gropp,O.M.Yaghi,Reticulating 1D Ribbons into 2DCovalent Organic Frameworks by Imine and Imide Linkages,J.Am.Chem.Soc.142(2020)2771–2776。

[0081] [4]P.J.Waller,S.J.Lyle,T.M.Osborn Popp,C.S.Diercks,J.A.Reimer,O.M.Yaghi,Chemical Conversion of Linkages in Covalent Organic Frameworks,J.Am.Chem.Soc.138(2016)15519–15522。

[0082] [5]S.J.Lyle,T.M.O.Popp,P.J.Waller,X.Pei,J.A.Reimer,O.M.Yaghi,Multistep Solid-State Organic Synthesis of Carbamate-Linked Covalent OrganicFrameworks,J.Am.Chem.Soc.(2019)。

Claims

1. A Janus covalent organic framework membrane with enhanced coordination, characterized in that: Its structural formula is shown in Formula I. Wherein, X is C or N, and R1 to R4 are independently -H or -OH.

2. The synergistic coordination enhanced Janus covalent organic framework membrane according to claim 1, characterized in that: R1 to R4 are independently -H or -OH, and are not -H or -OH at the same time.

3. The structure of the synergistically coordinated enhanced Janus covalent organic framework membrane according to claim 2 is:

4. The method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane according to any one of claims 1 to 3, wherein the specific steps include: a. Dissolve the aldehyde monomer in dichloromethane as the lower organic phase, and then slowly add acetic acid dropwise as the intermediate buffer aqueous phase; b. Dissolve the amine monomer in DMF (N,N-dimethylformamide) solution, and then slowly drop it onto the middle buffer water phase layer as the upper organic phase layer; c. The layered mixture is allowed to react at room temperature for 3 days, and then a solid product is obtained at the interface. The solid product is washed with water and ethanol in sequence to obtain a Janus covalent organic framework membrane with synergistic coordination enhancement.

5. The method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane according to claim 4, characterized in that: The mass volume ratio of the aldehyde monomer to dichloromethane in step a is 20 mg:60 mL to 60 mg:100 mL.

6. The method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane according to claim 4, characterized in that: The acetic acid described in step a is 6M.

7. The method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane according to claim 4, characterized in that: The mass volume ratio of the amine monomer to DMF in step b is 40 mg:30 mL to 80 mg:70 mL.

8. The method for preparing the synergistic coordination enhanced Janus covalent organic framework membrane according to claim 4, characterized in that: The molar ratio of the aldehyde monomer to the amine monomer in steps a and b is 1:1.1 to 1:1.

5.

9. Use of the synergistic coordination enhanced Janus covalent organic framework membrane according to any one of claims 1 to 3 in the preparation of Sr / Y separation materials.

Citation Information

Patent Citations

  • High-ultrasonic-reflection unmanned automobile coating composition and application thereof

    CN112194962A

  • Covalent organic framework, synthesis method thereof and application of covalent organic framework in uranium adsorption field

    CN116253848A

  • Preparation method of ultralight COF aerogel

    CN118240265A

  • Covalent organic frameworks and applications thereof in chemical reactions

    US20230001397A1